INTEGRASI SAINS DAN NILAI-NILAI ISLAM SEBAGAI EPISTEMOLOGI BARU DALAM PENGEMBANGAN PENDIDIKAN ISLAM - Hasan Asy’ari; Komarudin Sassi (Program Studi Pendidikan Agama Islam STIT al Urwatul Wutsqo Bulurejo Jombang, 2025)
The advancement of science and technology requires Islamic education to formulate a new paradigm that not only emphasizes normative religious aspects but also harmonizes modern scientific knowledge as an instrument for developing students’ competencies comprehensively. This article aims to examine the concept of integrating science and Islamic values as a paradigmatic foundation for the development of contemporary Islamic education. This study employs a library research approach combined with critical analysis of literature related to Islamic epistemology, educational philosophy, and models of knowledge integration. The findings indicate that the integration of science and Islam is not merely a curricular combination but the construction of an epistemological framework that perceives all forms of knowledge as a unified entity rooted in the principle of tawhid. Such integration can be actualized through curriculum design, pedagogical strategies, teacher competency development, and the revitalization of scholarly traditions. This study affirms that an integrative paradigm constitutes a strategic approach in shaping the ulūl al-albāb profile individuals with moral, spiritual, intellectual, and scientific excellence capable of responding to contemporary global dynamics.